Method for producing optical fiber preform, optical fiber preform, and optical fiber
By introducing a preheating process in the manufacturing process of optical fiber base material, the problem of difficulty in reducing the OH concentration near the start end of the sintering treatment is solved, and the optical fiber transmission loss is reduced and the optical fiber performance is achieved.
Patent Information
- Application Number
- CN202380066376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing optical fiber base material manufacturing method, the OH concentration near the start end of the sintering treatment is difficult to sufficiently reduce, resulting in a high transmission loss of the optical fiber.
Before the sintering step, a preheating process is performed. The specific steps include preheating the temperature environment of 800°C or more than 1300°C or less. The preheating time may be between 30 minutes and 480 minutes or less. Meanwhile, the ash-grain base material can be rotated and preheated in an environment containing N2, O2, Ar, He and Cl2 gases, and the radiant heat of the heater is propagated in the glass base material by providing a quartz glass handle to heat.
Through the preheating process, the OH concentration near the start end of the sintering treatment can be significantly reduced to reach less than 25 ppm, thereby reducing the transmission loss of the optical fiber and making it less than 0.29 dB/km.
Smart Images

Figure CN119894837A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing an optical fiber mother material, an optical fiber mother material, and an optical fiber. Background Art
[0002] As a method for manufacturing optical fiber base material, an external vapor deposition method is known. The external vapor deposition method is, for example, a method in which SiO2 obtained by reacting raw materials in a hydrogen-oxygen flame is blown onto a starting base material whose main component includes quartz glass and deposited to manufacture an ash base material. Then, the ash base material is subjected to the following process, and is simultaneously dehydrated and vitrified to be made into a transparent glass base material for optical fiber. The process is: in a furnace core tube formed of a heat-resistant material such as carbon or quartz, and a heater is provided on the outer periphery of the furnace core tube, the ash base material is heated at 1400 to 1600°C from one end to the other end in a mixed gas environment of circulating chlorine gas and inert gas. Summary of the invention
[0003] In the first aspect of the present invention, a method for manufacturing an optical fiber mother material is provided. The method for manufacturing an optical fiber mother material comprises: a deposition step, in which a soot mother material is obtained by attaching SiO2 particles to a starting mother material, wherein the starting mother material comprises silica glass and has a core portion with a higher refractive index and a cladding portion with a lower refractive index than the core portion; a sintering step, in which the soot mother material is dehydrated and vitrified in a dehydrated gas environment from one end thereof in sequence; and a preheating step, in which, before the sintering step, at least the soot mother material is preheated near the starting end of the sintering process. A method for manufacturing an optical fiber base material is provided.
[0004] The preheating process may be performed at a temperature lower than the sintering process.
[0005] The preheating step may be performed in a temperature environment of 800° C. to 1300° C.
[0006] The preheating step may be performed within a range of 30 minutes to 480 minutes.
[0007] In the preheating step, the soot base material may be preheated in an environment containing at least one of N 2 , O 2 , Ar, He and Cl 2 gases.
[0008] In the preheating step and / or the sintering step, the soot matrix may be rotated at a speed of 3 rpm or less.
[0009] Handles made of quartz glass are installed at both ends of the starting mother material including the quartz glass, and in the preheating step, the end surface of the handle on the starting end side of the sintering process and / or the side surface of the handle exposed to the outside of the ash mother material can be placed in the sintering furnace so that these surfaces are exposed to the radiant heat generated by the heater performing sintering, and the ash mother material is heated from the inside by propagating the radiation generated by the heater in the form of infrared rays in the handle and the starting mother material.
[0010] According to a second aspect of the present invention, there is provided an optical fiber preform comprising silica glass and having a core portion having a relatively high refractive index and a cladding portion having a refractive index lower than that of the core portion, wherein the average OH concentration in the radial direction is 25 ppm or less in 90% or more of the longitudinal direction.
[0011] In the entire section in the longitudinal direction, the average OH concentration in the radial direction may be 25 ppm or less.
[0012] The maximum value of the OH concentration in the radial direction may be 45 ppm or less.
[0013] According to a third aspect of the present invention, there is provided an optical fiber wherein the transmission loss of the optical fiber obtained from the optical fiber preform at a wavelength of 1383 nm is 0.29 dB / km or less.
[0014] In addition, the above-mentioned invention summary does not list all the essential features of the present invention. In addition, the combination of the feature group of these features can also constitute an invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 1 and 2 show a schematic structure of the soot matrix 4 in the present embodiment. Figure 2 The schematic structure of the sintering furnace 1 is shown. Figure 3 This is an explanatory diagram of the sintering step in Example 1. Figure 4 This is an explanatory diagram of the sintering step in Example 1. Figure 5 It is an explanatory diagram of a method for measuring the absorbance and OH concentration of the glass base material 4. Figure 6 It is an explanatory diagram of a method for measuring the absorbance and OH concentration of the glass base material 4. Figure 7 It is the absorbance (absorbance / diameter [cm -1 ]), and the wave number of transmitted infrared light [cm -1 ] is a curve graph of the relationship between . Figure 8 It indicates absorbance (absorbance / diameter cm-1 ) and the wave number of the transmitted infrared light [cm -1 ] is a curve graph of the relationship between . Fig. 9 is the wave number (cm) of the infrared light in Example 1 -1 ) at 3610cm -1 Up to 3740cm -1 The integral value A[cm -2 ] is a curve diagram of the distribution of the glass base material 4 in the length direction. Fig.10 This is a graph showing the OH concentration distribution in the radial direction at the sintering start end (longitudinal position 100%) of the glass base material 4 in Example 1. Fig.11 Graph showing the OH concentration distribution in the longitudinal direction of the glass base material 4 at the interface in Example 1. FIG. Fig.12 This is a graph showing the distribution of the OH concentration of the glass base material 4 in the longitudinal direction in Example 1. Fig.13 This is a graph showing the distribution of the OH concentration of the glass base material 4 in the longitudinal direction in Example 1. Fig.14 The length direction of the optical fiber mother material in Example 2 is between 3610 and 3740 [cm -1 The integral value of infrared absorption in the range of A[cm -2 ]’s curve graph. Fig.15 This is a graph showing the distribution of the OH concentration of the glass base material 4 in the longitudinal direction in Example 2. Fig.16 This is a table showing the average OH concentration and transmission loss in the radial direction of Examples 3 to 11. Fig.17 This is a table showing the OH concentration near the interface of Examples 12 to 16. Fig.18 The length direction of the glass base material 4 of the comparative example is between 3610 and 3740 [cm -1 The integral value of infrared absorption in the range of A[cm -2 ]’s curve graph. Fig.19 It is a graph showing the distribution of the OH concentration in the longitudinal direction at the interface in the glass base material 4 of the comparative example. Fig. 20 It is a graph showing the distribution of the radial average value of the OH concentration in the longitudinal direction of the glass base material 4 of the comparative example. Fig.21This is a graph showing the OH concentration distribution in the radial direction at the position of 100% of the sintering start end in the comparative example. DETAILED DESCRIPTION
[0016] The present invention will be described below by way of embodiments of the invention. The following embodiments do not limit the invention as claimed in the claims. The combination of features described in the embodiments is not necessarily essential to the solution of the invention.
[0017] Hereinafter, the method for producing the optical fiber preform in the present embodiment will be described in detail using examples and comparative examples.
[0018] [Example 1] [Deposition process] Figures 1 to 4 It is an explanatory diagram of the method for manufacturing the optical fiber preform according to the present embodiment. Figure 1 4 shows the general structure of the soot matrix 4 obtained by the deposition process. In order to manufacture the optical fiber matrix, first, SiO2 particles are deposited on the starting matrix whose main component is silica glass, so as to manufacture the soot matrix 4. Figure 1 The ash base material 4 has tapered portions at both ends. Figure 1 As shown, the soot matrix 4 has a straight body portion 4a, a tapered portion 4b, and a central axis 4c. In addition, the position on the diameter of the soot matrix 4 corresponding to the interface between the starting matrix and the deposited SiO2 fine particle layer (OVD layer: outside vapor deposition) is sometimes simply referred to as the "interface". The ratio of the diameter of the starting matrix to the diameter of the soot matrix 4 is about 0.3, so when the diameter of the soot matrix 4 is set to 1, the interface position is a position near 0.35 and 0.65 in the radial direction.
[0019] [Preheating process] Figure 2 1 shows the general structure of the sintering furnace 1. Regarding the optical fiber base material of Example 1, after the soot base material 4 is formed, the soot base material 4 is dehydrated and vitrified at the same time. Figure 2 As shown, the ash matrix 4 is set on the matrix receiving platform 5 of the turning support 6, and after turning, the ash matrix 4 is set to be located directly above the furnace core tube 3 of the sintering furnace 1. At this time, the ash matrix 4 is set above the furnace core tube 3 in such a way that the handle portion 7 on the lower end side of the ash matrix 4 is separated from the center of the main heater 2 by about 40 to 60 mm.
[0020] The ash parent material is set Figure 2After the sintering furnace 1 is shown, a preheating process is performed, that is, at least the vicinity of the sintering start end of the ash base material 4 is preheated in a temperature environment of 800°C to 1300°C for a period of 30 minutes to 480 minutes. Figure 2 The lower end of the straight body 4a of the ash parent material 4. The vicinity of the sintering start end refers to the area from the sintering start end side to the position of 10% in the length direction of the parent material. In other words, the vicinity of the sintering start end is the interval of 10% of the total length of the straight body from the lower end of the straight body 4a of the ash parent material 4 toward the inner side of the straight body 4a. In addition, it can be other values instead of 10%.
[0021] The bulk density of large ash particle base material 4 is 0.8g / cm 3 Below, the radius of the straight body 4a is 150 mm or more, and the length of the straight body 4a is 1500 mm or more. When the length of the straight body 4a is 1500 mm, the vicinity of the start end of the sintering process refers to a section of 150 mm from the lower end of the straight body 4a, and in the preheating step, preheating is performed so that the temperature of this section is 800° C. or more and 1300° C. or less.
[0022] In the preheating step, it is preferred to preheat the ash matrix 4 while rotating it at a speed of 3 rpm or less in an environment containing at least one of N2, O2, Ar, He and Cl2 gases. In addition, in the preheating step, it is preferred to place the end surface of the handle portion 7 on the starting end side of the sintering process and / or the side surface of the handle portion 7 exposed to the outside of the ash matrix 4 in the sintering furnace so that these surfaces are exposed to the radiant heat generated by the main heater 2 for sintering, and the ash matrix 4 is heated from the inside by propagating the radiation generated by the main heater 2 in the form of infrared rays in the handle portion 7 and the starting matrix.
[0023] In Example 1, as a preheating process, the heater temperature was set to 1100°C, and the top of the furnace tube 3 was kept open to the atmosphere for 2 hours, and then the tapered portion 4b at the lower end of the ash base material 4 was preheated before sintering and vitrification. The heater temperature refers to the value obtained by measuring the temperature at the upper and lower center positions of the main heater 2 using a thermocouple.
[0024] Thus, the ash mother material 4 heated in the preheating process can ensure sufficient time for the dehydration reaction to occur in the dehydrated gas environment before the temperature at which vitrification occurs is reached, even near the starting end of the process where vitrification begins earlier. Therefore, by performing a dehydration sintering process in the subsequent sintering process, an optical fiber mother material with a sufficiently reduced OH concentration near the starting end of the sintering process can be obtained.
[0025] [Sintering process] After the preheating process is completed, the sintering process is then carried out, that is, the ash matrix 4 is dehydrated and vitrified in a dehydrated gas environment from one end. In the sintering process, after the heater temperature is increased to about 1400 to 1600°C, the preheated ash matrix 4 is pulled downward at a moving speed of, for example, 5 mm / min in a mixed gas environment of chlorine gas and inert gas, and is passed through the heating zone of the heater, thereby dehydrating and vitrifying the ash matrix 4 to obtain a transparent glass matrix 4 for optical fiber (hereinafter, the same figure mark as the ash matrix is attached for explanation). In the sintering process, it is preferred to sinter the ash matrix 4 while rotating it at a speed of 3 rpm or less.
[0026] Figure 3 and Figure 4 1 is an illustration of the sintering process in Example 1. Figure 3 As shown, the handle 7 at the upper end of the ash base material 4 after the preheating process is completed is connected to the suspension shaft 9 of the base material suspension mechanism, and the suspension shaft 9 is connected and fixed to the ash base material 4 by a pin, as shown in FIG. Figure 4 As shown, the ash base material 4 is pulled down to the sintering start position, and the lid of the furnace core tube 3 is closed to start sintering. In addition, a disk-shaped heat shielding plate 8 made of opaque quartz with a thickness of 10 mm is attached to the handle 7 at the upper end of the ash base material 4 to carry out sintering. If such a heat shielding plate 8 is attached, the vicinity of the sintering end position is sufficiently heated, so that an opaque portion called an unmelted substance is less likely to be generated near the end of the sintering process.
[0027] In Example 1, after the start of sintering, He and Cl2 are supplied as dehydration gases at a predetermined flow rate, the heater temperature is set to 1500°C, and the soot matrix 4 is pulled down at a descending speed of 5.0 mm / min to dehydrate and vitrify the soot matrix 4, thereby manufacturing the glass matrix 4 for optical fiber. The glass matrix 4 for optical fiber contains silica glass and has a core portion with a relatively high refractive index and a cladding portion with a lower refractive index than the core portion.
[0028] Figure 5 and Figure 6 It is an explanatory diagram of a method for measuring the absorbance and OH concentration of the glass base material 4. Figure 5 4 is a side view of the glass base material 4 as viewed from the center axis 4c direction. Figure 6 4 is a top view of the glass base material 4 as viewed from a direction perpendicular to the central axis 4c. Figure 5 and Figure 6As shown, the infrared light measuring device 10 has an infrared light irradiation mechanism 11, an infrared light receiving mechanism 12, and a computing mechanism 13. A transparent glass base material 4 for optical fiber is arranged between the infrared light irradiation mechanism 11 and the infrared light receiving mechanism 12. The infrared light measuring device 10 uses, for example, Nicoletis 20 (registered trademark) FT-IR of Thermo Scientific. The spot size of the infrared light as the measuring light is, for example, 10 mm.
[0029] First, the method for measuring the absorbance of the glass base material 4 is described. In measuring the absorbance, Figure 5 As shown in FIG. 1 , the infrared light irradiation mechanism 11 irradiates the glass base material 4 with infrared light so that the infrared light serving as the measuring light passes through the center of the circle of the glass base material cross section. Figure 6 As shown in FIG. 1 , when infrared light is irradiated, the infrared light is perpendicular to the central axis 4c of the glass matrix 4. In this state, the wavelength of the infrared light is scanned, and the intensity of the transmitted infrared light received by the infrared light receiving mechanism 12 is measured. The wave number [cm -1 ] and absorbance. The absorbance per unit optical path length is calculated by dividing the obtained absorbance by the diameter [cm] of the glass matrix 4. The incident position of the infrared light is moved from one end to the other end of the straight body portion 4a of the glass matrix 4 along the length direction of the glass matrix 4, and the above measurement is repeated.
[0030] Figure 7 It is the absorbance per unit optical path length (absorbance / diameter [cm -1 ]), and the wave number of transmitted infrared light [cm -1 ] is a curve graph of the relationship between . Figure 7 The above relationship is shown at a specific position in the length direction of the glass mother material 4. Figure 7 In the curve graph, the wave number 3610 [cm -1 ] point and wave number 3740[cm -1 ], and calculate the difference between the straight line and the absorbance curve per unit optical path length, that is, the wave number 3610 [cm -1 ] and the wave number 3740cm -1 The integral value A[cm -2 The integral value A [cm] at each position in the longitudinal direction of the glass base material 4 is -2 ] changes. The integral value A[cm -2 ] is an index that changes with the degree of unmelted matter in the glass matrix 4. The less unmelted matter there is, the smaller the integral value A is. Therefore, the integral value A[cm -2 ]Preferably smaller.
[0031] Next, the method for measuring the OH concentration of the glass matrix 4 is described. In the method of manufacturing the glass matrix 4 by simultaneously performing dehydration and vitrification, there is a situation where vitrification occurs near the start end of the sintering process of the glass matrix 4 before the dehydration process is fully performed, which becomes one of the reasons for the instability of the optical characteristics of the glass matrix 4 in the longitudinal direction. In other words, if the glass matrix 4 is not fully dehydrated, the OH concentration near the start end of the sintering process of the glass matrix 4 becomes high, and the transmission loss of the optical fiber formed by drawing this part at a wavelength of 1383nm, which is known as the OH peak, becomes higher than usual. Therefore, it is important to more effectively dehydrate the vicinity of the start end of the sintering process.
[0032] The determination of the OH concentration of the glass matrix 4 is a destruction inspection of the glass matrix 4. At the measurement position in the length direction of the glass matrix 4, the glass matrix 4 is cut into discs to prepare a cylindrical sample with a thickness of 15 mm. Infrared light as the measurement light is incident from one bottom surface of the sample perpendicularly to the bottom surface and emitted from the other bottom surface. The infrared light measuring device 10 uses, for example, Nicolet is 20 (registered trademark) FT-IR from Thermo Scientific. The measurement light is incident on the sample through a 1 mm square opening on the hood. In this state, the wavelength of the infrared light is scanned, and the intensity of the transmitted infrared light received by the infrared light receiving mechanism 12 is measured. The wave number [cm -1 ] and absorbance. Calculate the absorbance difference with the absorbance data of the reference glass measured separately. Move the incident position of the infrared light from the circumference of the bottom circle along the diameter passing through the center of the circle to the circumference of the opposite side, and repeat the above measurement.
[0033] Figure 8 It is the difference between the absorbance and the wave number of the transmitted infrared light [cm -1 ] is a curve graph of the relationship between . Figure 8 The wave number is 3400 cm -1 Point and wave number 3800cm -1 A straight line is drawn from the points and a graph is shown showing the difference between the straight line and the actual measured absorbance. Figure 8 As shown, the curve representing the absorbance has a peak height α. Using the peak height α, the OH concentration of the glass matrix 4 is calculated using the following formula. When calculating the OH concentration of the glass matrix 4, the value of the OH molar absorption coefficient is 90 L / mol·cm, and the density of the glass matrix 4 is set to 2.2 g / cm 3 , calculated based on the Lambert-Beer law. Formula: OH concentration = (peak height α × OH molecular weight) / (OH molar absorption coefficient × density × optical path length)
[0034] On the diameter of the cylindrical glass mother material 4 cut into discs, more than 80 measurement points are set at equal intervals from the circumferential position along the diameter passing through the center of the circle to the circumferential position on the opposite side to measure the absorbance of infrared light, and the OH concentration at each measurement point is calculated. Then, the average value and maximum value of these OH concentrations are calculated, and the OH concentration distribution in the longitudinal direction of the glass mother material 4 is evaluated.
[0035] Fig. 9 is the wave number (cm) of the infrared light in Example 1 -1 ) at 3610cm -1 Up to 3740cm -1 The integral value A[cm -2 ] is a graph showing the distribution of the absorbance in the longitudinal direction of the glass matrix 4. For the glass matrix 4 produced by the manufacturing method of Example 1, the absorbance is measured at multiple positions in the longitudinal direction of the straight body portion 4a of the glass matrix 4 using an infrared light measuring device 10. Fig. 9 In the figure, the sintering start end of the straight body portion 4a of the glass base material 4 is represented as 100%, and the sintering end end is represented as 0%. Figure 2 The lower end of the glass matrix 4, and the sintering end is Figure 2 The upper end of the glass matrix 4. Fig. 9 As shown, the integral value A is 10 [cm -2 ] or less, infrared absorption is suppressed. In particular, at the position of 100% to 90% in the length direction near the start end of the sintering process, the integral value A is within 5 [cm -2 ] or less. This indicates that in the manufacturing process in Example 1, unmelted matter is suppressed.
[0036] Next, the OH concentration distribution in the radial direction is measured at a plurality of positions in the longitudinal direction of the straight body portion 4 a of the glass base material 4 . Fig.10 Graph showing the OH concentration distribution in the radial direction at the start of the sintering process of the glass base material 4 in Example 1. Fig.10 As shown, the interface position ( Fig.10 The OH concentration at the positions of 0.35 and 0.65 on the horizontal axis of ) was less than 10 ppm. Therefore, it can be seen that dehydration was sufficiently performed at the beginning of the sintering process.
[0037] Fig.11 Graph showing the OH concentration distribution in the longitudinal direction of the glass base material 4 at the interface in Example 1. Fig.11In FIG. 1 , the end of the sintering process of the straight body portion 4a of the glass base material 4 is represented as 0%, and the start end of the sintering process is represented as 100%. Fig.11 As shown, the OH concentration of the interface at the position of 100% to 90% in the length direction near the start end of the sintering process is equal to or lower than the OH concentration of the interface at the region of 20% to 80% of the straight body portion 4a, that is, lower than 20 ppm. Therefore, it can be seen that dehydration is sufficiently performed near the start end of the sintering process.
[0038] Fig.12 This is a graph showing the distribution of the OH concentration of the glass base material 4 in the longitudinal direction in Example 1. Fig.12 ] represents the average value of the radial OH concentration of the glass base material 4. Fig.12 As shown, the average OH concentration at the position of %100 to 90% in the length direction near the start end of the sintering process is less than 20 ppm, and the average OH concentration in the entire length direction of the glass base material 4 is less than 20 ppm. Therefore, it can be seen that dehydration is sufficiently performed near the start end of the sintering process.
[0039] Fig.13 This is a graph showing the distribution of the OH concentration of the glass base material 4 in the longitudinal direction in Example 1. Fig.13 The maximum value of the radial OH concentration of the glass base material 4 is shown in FIG. Fig.13 As shown, the maximum OH concentration in the region of 100% to 90% near the start of the sintering process is 25 ppm or less, and the maximum OH concentration is 30 ppm or less in the entire length direction of the glass base material 4. Therefore, it can be seen that dehydration is sufficiently performed near the start of the sintering process.
[0040] The transmission loss of the optical fiber drawn from the glass matrix 4 of Example 1 at a wavelength of 1383 nm was measured, and the transmission loss of the optical fiber corresponding to the vicinity of the sintering start end position of the straight body portion 4a of the glass matrix 4 was equal to or less than the transmission loss of the optical fiber in the region of 20 to 80% of the straight body portion 4a of the glass matrix 4, and was less than 0.295 [dB / km]. This is because dehydration was sufficiently performed near the sintering start end.
[0041] [Example 2] In Example 2, an ash mother material 4 identical to the glass mother material 4 of Example 1 is manufactured, and preheating and sintering are performed in the same sequence as in Example 1, except that the handle portion 7 at the upper end of the ash mother material 4 is sintered without installing the heat insulation plate 8.
[0042] Fig.14 The length of the glass base material 4 in Example 2 is 3610 to 3740 [cm-1 The integral value of infrared absorption in the range of A[cm -2 ] is a curve diagram. Fig.14 As shown, in Example 2, since unmelted matter is produced near the sintering end of the straight body portion 4a of the glass base material 4 (position 0 to 8% in the length direction), the portion becomes partially opaque, and therefore the infrared absorption of this portion cannot be measured. Fig.14 As shown, in the entire measurement interval, the integral value A is 10 [cm -2 ] or less. In particular, at the position of 100% to 90% in the length direction near the start end of the sintering process, the integral value A is within 5 [cm -2 ]the following.
[0043] Fig.15 This is a graph showing the distribution of the OH concentration of the glass base material 4 in the longitudinal direction in Example 2. Fig.15 The maximum radial value of the OH concentration of the glass matrix 4 is shown in FIG. Fig.15 As shown in the figure, the maximum value of the OH concentration is 25 ppm or less at the position of 100% to 90% in the length direction near the start end of the treatment, and the maximum value of the OH concentration is 30 ppm or less in the entire length direction of the glass base material 4. In addition, since unmelted matter is generated at the position of 4% in the length direction near the end end of the sintering treatment, the OH concentration cannot be measured in the entire radial direction. Therefore, the position of 4% in the length direction is indicated as ×. Fig.15 The maximum value of the OH concentration at a position near 4% in the longitudinal direction shown is the maximum value of the measurement result of the transparent portion where the OH concentration can be measured.
[0044] [Example 3 to Example 11] Nine soot base materials 4 were prepared in the same manner as in Example 1, and glass base materials 4 for optical fiber were manufactured under the conditions of setting the preheating temperature to 750°C, 850°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C, respectively, and setting the preheating time to 60 minutes. The sintering start end (100 to 98% interval) of the straight body portion 4a of the glass base material 4 was cut into discs and the radial OH concentration distribution was measured. In addition, the 98 to 90% interval of the straight body portion 4a was drawn to produce an optical fiber, and the transmission loss of the optical fiber at a wavelength of 1383nm was measured.
[0045] Fig.16 TABLE 1 is a table showing the average OH concentration and transmission loss in the radial direction of Examples 3 to 11. Fig.16As shown, in Example 3 with a preheating temperature of 750°C, the average OH concentration was 30 ppm, and the transmission loss of the optical fiber was 0.295 dB / km. In addition, in Example 11 with a preheating temperature of 1400°C, the average OH concentration was 40 ppm, and the transmission loss of the optical fiber was 0.31 dB / km. In Examples 4 to 10 with a preheating temperature of 800°C to 1300°C, the average OH concentration was below 20 ppm, and the transmission loss of the optical fiber was also below 0.29 dB / km.
[0046] In summary, when the preheating temperature is higher than 750°C and lower than 1400°C, the average OH concentration and the transmission loss of the optical fiber can obtain good results. In addition, it is believed that when the preheating temperature is below 750°C, a sufficient preheating effect cannot be obtained, and therefore a good result cannot be obtained. In addition, it is believed that when the preheating temperature is above 1400°C, the preheated part of the SiO2 microparticle porous body becomes dense, resulting in the inability of the dehydrated gas to fully penetrate during the sintering process, and therefore a good result cannot be obtained. Therefore, the preheating temperature is preferably a temperature exceeding 750°C, and more preferably above 800°C. In addition, the preheating temperature is preferably less than 1400°C, and more preferably below 1300°C.
[0047] [Example 12 to Example 16] Fig.17 TABLE 1 is a table showing the OH concentration near the interface of Examples 12 to 16. Five soot base materials 4 were prepared in the same manner as in Example 1, and glass base materials 4 for optical fiber were manufactured under the conditions of setting the preheating temperature to 800°C and the preheating time to 480 minutes, 300 minutes, 90 minutes, 30 minutes, and 10 minutes, respectively. The sintering start end (100% to 98%) of the straight body portion 4a of the glass base material 4 was cut into discs, and the OH concentration distribution near the interface between the starting base material and the OVD layer was measured.
[0048] like Fig.17 As shown, in Example 16 where the preheating time is 10 minutes, the OH concentration near the interface is 35 ppm. Based on this result, it can be seen that when the preheating time is 10 minutes, the OH concentration near the interface is not sufficiently reduced because the heating has not yet been fully carried out to the center of the ash base material 4. In Examples 12 to 15, the OH concentration near the interface is less than 20 ppm. Therefore, it can be seen that in order to heat to the center, it is preferred to spend more than 30 minutes of preheating time. On the other hand, even if the preheating time exceeds 480 minutes, there is no trend of a significant reduction in the OH concentration. For efficiency reasons, it is preferred to set the preheating time to within 480 minutes.
[0049] [Comparative Example] The soot base material 4 was sintered in the same manner as in Example 1 to produce an optical fiber base material, except that the preheating step was not provided. Fig.18 The length direction of the glass base material 4 of the comparative example is between 3610 and 3740 [cm -1 The integral value of infrared absorption in the range of A[cm -2 ] is a curve diagram. Fig.18 As shown, in particular, at the position of 100% to 90% in the length direction near the start end of the sintering process, the integral value A is more than 10 [cm -2 ]. This indicates that unmelted matter was generated because no preheating step was provided in the comparative example.
[0050] Fig.19 Graph showing the distribution of OH concentration at the interface in the length direction of the glass mother material 4 of the comparative example. The glass mother material 4 of the comparative example was cut into discs at multiple positions in the length direction, and the distribution of OH concentration in the radial direction of each cut glass mother material 4 was measured. Fig.19 As shown, the OH concentration of the interface at the position of 100% to 90% in the longitudinal direction near the sintering start end is higher than that in the region of 20% to 80%. Therefore, it is known that the dehydration near the sintering start end is not sufficiently performed because the preheating step is not provided.
[0051] Fig. 20 Graph showing the distribution of the radial average value of the OH concentration in the glass matrix 4 of the comparative example in the longitudinal direction. Fig. 20 As shown in FIG. 1 , the average OH concentration in the region of 100 to 90% near the start of the sintering process is more than 25 ppm. Therefore, it is known that dehydration is not sufficiently performed near the start of the sintering process because the preheating step is not provided.
[0052] Fig.21 Graph showing the OH concentration distribution in the radial direction at the 100% position of the sintering start end of the comparative example. Fig.21 As shown, it can be seen that at the interface position ( Fig.21 The OH concentration is 30 ppm or more at the positions of 0.35 and 0.65 on the horizontal axis. In addition, the transmission loss of the optical fiber obtained by drawing the glass base material 4 of the comparative example near the processing start end 98% to 90% is 0.295 [dB / km] or more at a wavelength of 1383 nm. This is because the dehydration near the sintering start end cannot be fully performed.
[0053] [Effect] According to the method for manufacturing an optical fiber base material in the above-described embodiment, a preheating step is provided before the sintering step, that is, the soot base material 4 is preheated at least near the sintering start end in a temperature environment of 800° C. to 1300° C. for a period of 30 minutes to 480 minutes. Thus, the OH concentration near the sintering start end can be reduced to 20 ppm or less, thereby reducing the transmission loss of the optical fiber.
[0054] The present invention has been described above using the embodiments, but the protection scope of the present invention is not limited to the scope described in the embodiments. It is clear to those skilled in the art that various changes or improvements can be made to the embodiments. According to the description of the claims, such changed or improved embodiments can also be included in the protection scope of the present invention.
[0054] It should be noted that the execution order of each process such as actions, steps, steps and stages in the devices, systems, programs and methods shown in the claims, specifications and drawings can be implemented in any order unless it is specifically stated as "prior to", "before", etc., and the output of the previous process is not used in the subsequent process. Even if the action flow in the claims, specifications and drawings is described using "first", "next", etc. for convenience, it does not mean that it must be implemented in this order. [Explanation of Reference Numerals] 1: Sintering furnace 2: Main heater 3: Furnace core tube 4: Ash parent material (glass parent material) 4a: Straight body part 4b: Conical part 4c: Central axis 5: Base material receiving platform 6: Flip the prop 7: Handle 8: Heat insulation board 9: Suspension shaft 10: Infrared light measuring device 11: Infrared light irradiation mechanism 12: Infrared light receiving mechanism 13: Operation mechanism.
Claims
1. A method for manufacturing an optical fiber mother material, comprising: A deposition step of obtaining a soot matrix by attaching SiO2 particles to a starting matrix, wherein the starting matrix comprises silica glass and has a core portion having a relatively high refractive index and a cladding portion having a lower refractive index than the core portion; a sintering step, in which the ash parent material is dehydrated and vitrified in sequence from one end thereof in a dehydrated gas environment; and The preheating step preheats at least the vicinity of the sintering start end of the soot base material before the sintering step. 2 . The method for manufacturing an optical fiber preform according to claim 1 , wherein the temperature at which the preheating step is performed is lower than the temperature at which the sintering step is performed. 3 . The method for producing an optical fiber preform according to claim 1 , wherein the preheating step is performed under a temperature environment of 800° C. to 1300° C. 4 . The method for producing an optical fiber preform according to claim 1 , wherein the preheating step is performed within a range of 30 minutes to 480 minutes.
5. The method for manufacturing an optical fiber base material according to claim 1, wherein in the preheating step, the soot base material is preheated in an environment containing at least one of N2, O2, Ar, He and Cl2 gases.
6. The method for manufacturing an optical fiber preform according to claim 1, wherein in the preheating step and / or the sintering step, the soot preform is rotated at a speed of 3 rpm or less.
7. The method for manufacturing an optical fiber preform according to claim 1, wherein handles made of quartz glass are attached to both ends of the starting preform including the quartz glass, and In the preheating step, the end face of the handle at the starting end of the sintering process and / or the side face of the handle exposed to the outside of the ash matrix are placed in a sintering furnace so that these faces are exposed to the radiant heat generated by the heater performing sintering, and the ash matrix is heated from the inside by allowing the radiation generated by the heater to propagate in the form of infrared rays within the handle and the starting matrix.
8. An optical fiber base material comprising silica glass and having a core portion with a relatively high refractive index and a cladding portion with a refractive index lower than that of the core portion, wherein the average OH concentration in the radial direction is 25 ppm or less in a section of more than 90% in the longitudinal direction. 9 . The optical fiber preform according to claim 8 , wherein the average OH concentration in the radial direction is 25 ppm or less throughout the entire section in the longitudinal direction. 10 . The optical fiber preform according to claim 8 , wherein a maximum value of the OH concentration in the radial direction is 30 ppm or less.
11. An optical fiber obtained by using the optical fiber preform according to claim 8, wherein the transmission loss at a wavelength of 1383 nm is 0.29 dB / km or less.